Choir Singing and Music Appreciation Training Enhances Unaided Speech-in-Noise Perception and Frequency Following Responses for Older Adult Hearing Aid Users: A Randomized Controlled Trial - Lo, Chi Yhun; Dubinsky, Ella; Gilmore, Sean A.; Wright-Whyte, Kay; Singh, Gurjit; Russo, Frank A. (Seminars in Hearing, 2025)
Hearing aids (HAs) improve speech perception in quiet environments but remain less effective in noisy conditions, posing significant communication challenges for older adults. Musical training has been proposed as a potential intervention to enhance speech-in-noise (SIN) perception through auditory neuroplasticity. This randomized controlled trial investigated the impact of a 14-week music-based intervention on auditory outcomes in older adult HA users. Forty-seven participants were randomly assigned to one of three groups: choir singing (n = 14; active music training), music appreciation (n = 13; passive music engagement), or a do-nothing control group (n = 12). Primary outcome measures included SIN perception, while secondary outcomes assessed pitch perception and frequency-following response (FFR). Results revealed that participants in the choir singing group demonstrated significant improvements in unaided SIN perception and FFR compared to the do-nothing control group, but not in aided conditions. No significant differences were found between the choir singing and music appreciation groups, suggesting that both active and passive music engagement may enhance auditory processing. These findings highlight the potential of music-based training as a complementary intervention for older adults with hearing loss, though further research is needed to establish long-term benefits and effects in everyday listening conditions.
Keywords: speech-in-noise perception; music training; hearing aids; older adults; frequency following response